Surface Modification of Chitosan Membrane with Ag as Additive - rasli, nurul izwanie (Enhanced Knowledge in Sciences and Technology, 2022)
The flat sheet membrane of chitosan/silver membrane was prepared via phase inversion technique. In this study, the membrane was added with different composition of silver nitrate as an additive. The analysis includes Fourier-Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), membrane porosity (%) and elemental analysis via Energy Dispersive X-Ray (EDX). Results showed that the addition of silver nitrate promotes the formation of dense spongy structure of the membrane and hence increases the macrovoids formation. These phenomena then lead to the decreasing in membrane porosity. The addition of silver nitrate reduced the membrane porosity and increased the mean pore size of the fabricated membrane. The chitosan membrane without silver nitrate has the highest membrane porosity which is 38.58 % while membrane with 0.75 wt.% of silver nitrate has the lowest which is 14.38%. Overall, the study shows that silver nitrate addition exhibited chitosan-based membrane enhancement in term of its morphology.